2009
DOI: 10.1017/s1368980009991777
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of breast-feeding in a Finnish birth cohort

Abstract: Objective: To assess milk feeding on the maternity ward and during infancy, and their relationship to sociodemographic determinants. The validity of our 3-month questionnaire in measuring hospital feeding was assessed. Design: A prospective Finnish birth cohort with increased risk to type 1 diabetes recruited between 1996 and 2004. The families completed a follow-up form on the age at introduction of new foods and age-specific dietary questionnaires. Setting: Type 1 Diabetes Prediction and Prevention (DIPP) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
40
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 43 publications
7
40
1
1
Order By: Relevance
“…In agreement with previous observations [18,20,45], our results also indicated that maternal smoking during pregnancy and child's low birthweight (\2500 g) decreased the likelihood of ever XBR and XBR for 6 months, respectively. A review of maternal smoking and breastfeeding suggested that psychosocial factors rather than physiological ones are largely responsible for poor lactation performance in smoking women [46].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous observations [18,20,45], our results also indicated that maternal smoking during pregnancy and child's low birthweight (\2500 g) decreased the likelihood of ever XBR and XBR for 6 months, respectively. A review of maternal smoking and breastfeeding suggested that psychosocial factors rather than physiological ones are largely responsible for poor lactation performance in smoking women [46].…”
Section: Discussionsupporting
confidence: 92%
“…9 Existing research consistently documents an association between longer duration of exclusive breastfeeding and longer duration of any breastfeeding, and shorter duration of exclusive breastfeeding is associated with early breastfeeding cessation. [10][11][12][13][14][15][16] However, methods used to define duration of exclusive breastfeeding vary. Most studies dichotomized or categorized durations ranging from 1 day through 4 months postpartum rather than treating exclusive breastfeeding duration as a continuous variable.…”
mentioning
confidence: 99%
“…The risk for major depression was considerably increased in bottle-fed compared to breast-fed subjects (OR: 2.00; CI: 1.28–3.12; table 1). Controlling for risk factors of depression and maternal education known to be related to breast-feeding [10], we found bottle-feeding (B = 1.12, p = 0.005), but not age, gender and maternal education (∣B∣ ≤ 0.30, NS) to be related to depression.…”
Section: Introductionmentioning
confidence: 64%